2020
DOI: 10.1002/eap.2191
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling landscape and local drivers of ground‐dwelling beetle community assembly in an urban ecosystem

Abstract: Community assembly is the process by which local communities are organized and maintained from the regional species pool. Understanding processes of insect assembly are of interest in "shrinking" cities where vacant land has become abundant as a result of protracted economic decline and population loss. Vacant land represents a viable conservation space for insects such as beetles that contribute to ecosystem services including pest suppression, decomposition, and nutrient cycling. However, the inherent hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 129 publications
3
12
0
Order By: Relevance
“…All trapping methods combined caught an estimated 85% -88% of the taxa present in the community based on species accumulation curves. The observed sampling efficiency is similar to that found in other studies of this type: a ground beetle study in nearby Cleveland, Ohio found that their unbaited pitfall traps collected 69% of the estimated species richness in one year of study and 66% the next [85]. In a sandfly trapping comparison study in Mexico, Jackknife order 2 estimates predicted 85% of taxa were found between all trap types [86].…”
Section: Discussionsupporting
confidence: 84%
“…All trapping methods combined caught an estimated 85% -88% of the taxa present in the community based on species accumulation curves. The observed sampling efficiency is similar to that found in other studies of this type: a ground beetle study in nearby Cleveland, Ohio found that their unbaited pitfall traps collected 69% of the estimated species richness in one year of study and 66% the next [85]. In a sandfly trapping comparison study in Mexico, Jackknife order 2 estimates predicted 85% of taxa were found between all trap types [86].…”
Section: Discussionsupporting
confidence: 84%
“…Dispersal capacity of species contributes to processes of community assembly at landscape and local scales, including patterns of probabilistic dispersal and recolonization following natural and anthropogenic disturbances. Studies of arthropod community assembly have often found that a combination of stochastic (neutralbased) and deterministic (niche-based) processes shape patterns of assembly (Thompson and Townsend 2006, Farnon Ellwood et al 2009, Rominger et al 2009, Ferrenberg et al 2019, Perry et al 2020), but disturbances can mediate the relative importance of these mechanisms. For example, following tree mortality caused by bark beetles, the relative importance of deterministic processes related to plant and soil habitat characteristics increased in strength for grounddwelling arthropods, while stochastic processes related to dispersal limitations increased for soildwelling arthropods (Ferrenberg et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Legacy cities are characterized by long-term economic disinvestment (Martinez-Fernandez et al 2012; Haase et al 2014) and vacancy shapes their landscape pattern by creating dynamic mosaics of occupied and abandoned structures, and patches of formerly occupied vacant land (Gardiner et al 2013;Sampson et al 2017). Vacant lots provide season long forage for urban bees from urban spontaneous vegetation (Perry et al 2020), and these habitats can support species rich bee communities. Legacy cities have also become targets for green investments, such as the creation of pocket prairies, urban farms, and rain gardens on vacant land, often with the explicit aim or stacked bene t of supporting pollinator health (Gardiner et al 2013; Rega-Brodsky and Nilon 2016; Cha n et al 2016; Anderson and Minor 2017; Sivakoff et al 2018).…”
Section: Introductionmentioning
confidence: 99%